Management Accounting and Control System - Dahal, Rewan Kumar (NCC Journal, 2018)
A larger entity of the cost management system which assists executives in fulfilling organizational objectives is known as management accounting and control system (MACS). It is used for planning, monitoring and control of different organizational activities, to optimize the use of resources, to support the process of decision making and to the performance evaluation process. The scope of the MACS can be divided into two broad groups: technical considerations and behavioral considerations. Technical considerations fall into two categories: (i) the relevance of information generated and (ii) the scope of the system like the value chain, total life cycle costing, target costing, kaizen costing, benchmarking, balanced scorecard etc. whereas the behavioral consideration involves individuals and their behavior within organizations.NCC JournalVol. 3, No. 1, 2018, Page: 153-166